2017
DOI: 10.1016/j.jand.2017.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Eating Practices and Attitudes of Registered Dietitian Nutritionists

Abstract: Background: Dieting is proven to be ineffective for weight management. Research shows that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Two surveys of U.S. dietitians’ attitudes towards IE found attitudes towards professional use of IE principles differed by personal level of IE endorsement. Simon found low versus high IE practice endorsement resulted in scores of 9.50 versus 11.37 for knowledge and 24.00 versus 26.53 for attitude respectively (both p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two surveys of U.S. dietitians’ attitudes towards IE found attitudes towards professional use of IE principles differed by personal level of IE endorsement. Simon found low versus high IE practice endorsement resulted in scores of 9.50 versus 11.37 for knowledge and 24.00 versus 26.53 for attitude respectively (both p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Two surveys of U.S. dietitians’ attitudes towards IE found attitudes towards professional use of IE principles differed by personal level of IE endorsement. Simon found low versus high IE practice endorsement resulted in scores of 9.50 versus 11.37 for knowledge and 24.00 versus 26.53 for attitude respectively (both p < 0.01). A large study of 22, 542 USA‐based dietitians by Schaefer et al found a mostly positive attitude towards WN practice, with 37% of respondents indicating they ‘support’, and 36.7% indicating they ‘strongly support’ an IE approach.…”
Section: Discussionmentioning
confidence: 99%